Frailty in Portuguese Older Patients From Convalescence Units: A Cross-Sectional Study - Pinto, M (2022)
Background: Frailty is a common geriatric syndrome, associated with adverse clinical outcomes. Nevertheless, studies about frailty in continuous care units are scarce. In this way, this study aimed to assess frailty in older patients admitted in convalescence units (CUs) and analyze its association with demographic, social and clinical characteristics. Methods: This cross-sectional study included older patients admitted in eight CUs of the Integrated Continued Care National Network in Northern Portugal. Exclusion criteria were: total ≤ 11 in Glasgow coma scale, < 10 in mini-mental state examination or being unable to communicate. A comprehensive protocol was administered to assess health-related and lifestyle characteristics, comorbidity, dependence on activities of daily living (ADL), depressive and anxiety symptoms, cognition, and socio-familial risk. Frailty was assessed by Tilburg frailty indicator (TFI). Results: A sample of 165 patients was included (median age = 77; 65% female), with 80% classified as frail, mostly women (P = 0.002), widowed (P = 0.016), shorter (P = 0.005), feeling more tired (P < 0.005) and with less energy (P < 0.005). Also, these patients reported more vision problems (P = 0.006), difficulties in walking (P = 0.022) and climbing stairs (P = 0.029), pain (P = 0.004), falls (P = 0.046), non-alcohol use (P = 0.043) and non-physical activity (P = 0.032). Frail patients had a higher number of previous hospitalizations (P = 0.018), comorbidity (P = 0.006), dependence on instrumental (P < 0.001) and basic (P = 0.006; P < 0.001) ADL, depressive (P < 0.001) and anxiety (P = 0.002) symptoms. After adjusting for covariates, frailty was associated with females (adjusted odds ratio (aOR) = 4.45, P = 0.011), vascular disease (aOR = 4.40, P = 0.040), vision problems (aOR = 10.85, P < 0.001), high dependency on instrumental ADL (aOR = 0.74, P = 0.002), and depressive symptoms (aOR = 1.37, P = 0.001). Conclusions: Frailty is high among older patients in CUs, particularly in females, with vascular disease, vision problems, instrumental ADL dependence and depressive symptoms. Thus, frailty should be screened, and preventive and therapeutic measures should be considered for those at high risk, in order to minimize possible negative consequences. © The authors | Journal compilation J Clin Med Res and Elmer Press Inc™ | www.jocmr.org This article is distributed under the terms of the Creative Commons Attribution Non-Commercial 4.0 International License, which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited